2018
DOI: 10.3390/ijerph15112346
|View full text |Cite
|
Sign up to set email alerts
|

The Reverse Shock Index Multiplied by Glasgow Coma Scale Score (rSIG) and Prediction of Mortality Outcome in Adult Trauma Patients: A Cross-Sectional Analysis Based on Registered Trauma Data

Abstract: The reverse shock index (rSI) multiplied by Glasgow Coma Scale (GCS) score (rSIG), calculated by multiplying the GCS score with systolic blood pressure (SBP)/hear rate (HR), was proposed to be a reliable triage tool for identifying risk of in-hospital mortality in trauma patients. This study was designed to externally validate the accuracy of the rSIG in the prediction of mortality in our cohort of trauma patients, in comparison with those that were predicted by the Revised Trauma Score (RTS), shock index (SI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 38 publications
3
34
1
11
Order By: Relevance
“…The ISS, AIS, ward, and intensive care unit (ICU) stay were not normally distributed and were, therefore, displayed by median (IQR). The median (IQR) of ISS and AIS was significantly higher in the mortality group than in the survival group (25 11,17-28 and 16 [16][17][18][19][20][21][22][23][24][25] vs 18 [16][17][18][19][20][21][22][23][24][25] and 16 [9][10][11][12][13][14][15][16] , respectively). Traffic accident (45.3%) was the most common injury mechanism, with motorcycle accidents accounting for 34.7% despite wearing helmets according to the Taiwan traffic regulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ISS, AIS, ward, and intensive care unit (ICU) stay were not normally distributed and were, therefore, displayed by median (IQR). The median (IQR) of ISS and AIS was significantly higher in the mortality group than in the survival group (25 11,17-28 and 16 [16][17][18][19][20][21][22][23][24][25] vs 18 [16][17][18][19][20][21][22][23][24][25] and 16 [9][10][11][12][13][14][15][16] , respectively). Traffic accident (45.3%) was the most common injury mechanism, with motorcycle accidents accounting for 34.7% despite wearing helmets according to the Taiwan traffic regulations.…”
Section: Resultsmentioning
confidence: 99%
“…The rSIG uses easily obtainable physiological variables (SBP, HR, and GCS) and is simple to calculate. A study conducted by SC Wu et al showed the best rSIG cutoff point was 14.8 for trauma patients with head injury, with 86.8% sensitivity and 70.7% specificity 23 . Similarly, our study found that rSIG is a useful tool to predict mortality in adult severe trauma patients with head injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum possible score on the GCS is 15 and the minimal possible -3, the lower the score the more severe the consciousness disorders. The final scores can be divided into three categories of disorders of consciousness: severe (GCS 3-8), moderate (GCS 9-12) and mild (GCS 13-15) [15].…”
Section: Methodsmentioning
confidence: 99%
“…AIS is the fundamental basis of several severity scoring systems, such as the Injury Severity Score (ISS) [2], the Maximum Abbreviated Injury Score [3], the New Injury Severity Score (NISS) [4,5], and the Exponential Injury Severity Score [5]. The most commonly used prediction model for survival probability of trauma patients, the Trauma and Injury Severity Score (TRISS) [6][7][8], is also calculated based on the ISS.…”
Section: Introductionmentioning
confidence: 99%